TINGKAT PEMAHAMAN GURU MI MUHAMMADIYAH KALIBEBER TERHADAP PENERAPAN PEMBELAJARAN SANTIFIK - Neli Agustina; Izzatul Fitriani; Kharistia Capriati (MERDEKA : Jurnal Ilmiah Multidisiplin, 2024)
In the history of curriculum development in Indonesia, the Ministry of National Education Research and Development since 1979 has pioneered this prestigious development program in the Supervision Project and CBSA (Active Student Learning Method). The results of this project were then replicated in a number of regions and developed through training of teaching staff throughout Indonesia. This effort, which began at the elementary school level, then encouraged the implementation of an active learning approach at the secondary school level. The results of these efforts were gradually integrated into the 1984 Curriculum, the 1994 Curriculum, and the 2004 Competency-Based Curriculum, which was followed by the Content Standards which are better known as the 2006 Educational Unit Level Curriculum (KTSP) (Mushfiqon and Nanda, 2015) . The scientific approach is a learning model that provides space for students to explore and elaborate on the material being studied. Apart from that, this education model also provides students with the opportunity to hone their abilities through learning activities designed by the teacher (Rusman, 2015). The scientific approach method is a teaching and learning process that is designed in such a way that students actively construct concepts and laws through manifestation in various stages of observing (to identify or find problems), describing problems, formulating hypotheses, collecting data using various techniques, analyzing data, draw conclusions, and communicate the concepts, laws or principles found (Karar and Yenice, 2012). This research uses a survey method. The data was obtained using a questionnaire/questionnaire. The research was carried out at MI Muhammadiyah Kalibeber, Mojotengah District, Wonosobo Regency with all teachers who were still active in teaching and learning activities. Bearing in mind that the target of this research is all teachers at MI Muhammadiyah Kalibeber, Mojotengah District, Wonosobo Regency, totaling 7 teachers. This research uses three types of data analysis, namely percentage analysis, chi square (x2), and Pearson product moment correlation. Percentage analysis is used to describe factors that influence teacher understanding. Chi square and product moment analysis to find out how much influence these factors have on teachers' understanding and response to the scientific approach. Learning with a scientific approach is a learning process that is designed in such a way that students actively construct concepts, laws or principles through the stages of observing (to identify or find problems), describing problems, proposing or compiling hypotheses, collecting data using various techniques, analyzing data, draw conclusions and communicate “discovered” concepts, laws or principles.